Lo stanzone dei ricordi: dal cambiamento alla trasformazione - Vari, Autori (Il sogno della farfalla, 2018)
The authors of the article describe their psychotherapeutic work in a community for patients affected by psychosis, located in South Rome. The therapeutic practice is carried out within a therapeutic community that has been conceived based on the British model of community and a theoretical and methodological approach based on Human Birth Theory, developed by the psychiatrist Massimo Fagioli. Starting from the concept of the annulment pulsion as the main dynamic leading to the onset of mental illnesses, the authors claim that there cannot be a true change in patients affected by mental illnesses unless there is a deep change in their non-conscious dynamics. This is because mental illness essentially lies in non-conscious reality. In order to support their thesis, the authors describe their clinical practice which they have been carrying out for more than ten years now. They conclude the article by claiming that, when a positive development occurs thanks to the therapeutic relationship, the old pathological dynamics become inanimate objects inside “The large room of recollections” as it was defined by Massimo Fagioli in his La marionetta e il burattino.